Prinsip-Prinsip Good Corporate Governance dan Tingkat Kepuasan Muzakki dalam Menyalurkan Zakat pada LAZ di Kabupaten Jember - Yulinartati Yulinartati; Adella Lagareta Iswanto; Suwarno Suwarno (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2020)
ABSTRACT This study aims to determine the effect of good corporate governance principles on the level of muzaki satisfaction in distributing zakat to LAZ in Jember Regency. Distribution of zakat funds at LAZ is now growing, researchers want to know the organizational governance that has been implemented at the Amil Zakat Institution can increase the satisfaction of muzaki in distributing zakat. This study examines the effect of the principles of good corporate governance consisting of transparency, accountability, responsibility, independence and fairness to the level of satisfaction of muzaki in distributing zakat. The sample in this study amounted to 97 respondents namely muzaki who have paid zakat at LAZ in Jember Regency. Data collection techniques using interviews and questionnaires. The results of hypothesis testing show that the principles of good corporate governance, namely transparency, accountability, responsiveness, independence, and reasonableness have a positive and significant effect on the level of satisfaction of muzaki in distributing zakat. Keywords: Good Corporate Governance, Accountability, Transparency, Responsibility, Independence, Fairness / Fairness, Zakat, Muzaki Satisfaction.